Students' Perception about Learning Assessment in Higher Education - Holmes Rodríguez-Espinosa; Luis Fernando Restrepo-Betancur; Gloria Cristina Luna-Cabrera (Universidad Nacional, Costa Rica, 2016)
This research aimed to know university students' perception about learning assessment carried out by their teachers, their level of objectivity and skill, among other aspects. The study was conducted in Medellin, Colombia, between January and July 2015. A final sample size of 400 university students from public and private institutions, randomly selected, was used. The data analysis was carried out by using multivariate analysis of variance (MANOVA) with orthogonal-type canonical contrast, factor analysis, and one-dimensional type frequency analysis. It was found that university students have a good perception about the assessment practices of their teachers. Likewise, highly significant differences between men and women in their perception of learning assessment were identified. Students consider that learning assessment practices have contributed to improve their learning and are in accordance with the learning objectives. Nevertheless, most students have felt that their teachers are not objective in evaluation and they often use questions that confuse students, and very theoretical questions without application to practice. A lack of non-traditional assessment practices, such as peer assessment, self-assessment as well as virtual platforms use for assessments, was found. These findings imply the need to improve teacher training on assessment skills to allow them to plan evaluation as a strategy to improve learning, involving students in an active way.